Clinical and laboratory features of typhoid fever in childhood - Sylvia Retnosari; Alan R. Tumbelaka; Arwin P. Akib; Sri Rezeki Hadinegoro (Indonesian Pediatric Society, 2001)
The aims of the study were to review the clinical features of patient with suspected typhoid fever, to obtain features of the blood culture results, Widal, Typhidot tests and to identify the relationship between/prior antibiotic administration with laboratory findings. The study had been conducted since January 1, 1999 till January 31, 2000 with inclusion criteria (1) age of patient was 3 to 14 years, (2) patient with diagnosis of suspected typhoid fever and (3) gave consent to participate in the present study. Thirty-six patients were eligible for this study and the result showed that typhoid fever was encountered more commonly in girls with the most prevalent onset was in age 5 to 9 years and duration of fever was less than 8 days. Gastrointestinal tract disturbance was the most frequent complain after fever. Most patient showed negative results in blood culture examination and Widal test, and gave positive results in Typhidot/Typhidot M test as well. Antibiotic administration tended to influence blood culture and Widal test as to need consideration in evaluation of laboratory results. However, a conclusion still could not be drawn definitively that further study with adequate sample number and positive blood culture as criteria inclusion was needed.